EFFECT OF GAMMA IRRADIATION ON MICROBIAL CELLULOSE MEMBRANE FOR APPLICATION IN GUIDED BONE REGENERATION (GBR) - Darwis, Darmawan (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2013)
The synthesis and effect of gamma irradiation on characteristics of microbial cellulose membrane have been evaluated. Microbial cellulose gel (nata de coco) was produce using bacteria Acetobacter xylinum incubated in bacterial growth medium containing coconut water as a micro nutrient source. Microbial cellulose membrane was prepared using mould compression at 120°C for 5 minutes. The membranes were irradiated using gamma rays with doses of 25 and 50 kGy respectively at dose rate of 10 kGy/h. Several parameters such as water absorption, surface morphology, thermal and mechanical properties of un- irradiated and irradiated membranes were analyzed. The results showed that optimum production of microbial cellulose by A. Xylinum is 10 to 12 days at incubation temperature of 30°C and pH 4. Chemically treatments of MC membrane by NaOH and NaOCl solution were effective to remove the bacteria contaminant, bacterial cells embedded in the polymer net and endotoxin which occurred during cellulose production as well as produced membrane with more white colour. Water absorptionproperties of MC membranes showed maximum value at immersion temperature of 25°C, 37°C and 50°C were 110, 137 and 140 %, respectively. Water absorption of MC membrane decreases by increasing irradiation dose. Microscopic photograph of MC membrane showed that the membrane was consisted of interconnected nano to micro porous structures with diameter ranging from 0.05 to 0.5 μm. Thermal properties of MC showed that decomposition temperature of un-irradiated and irradiated MC membrane at dose of 25 and 50 kGy were 328°C, 328°C and 295°C, respectively. Tensile strength of un-irradiated MC membrane in dry state was 102 MPa. Irradiation at 25 and 50 kGy reduced tensile strength to become 85 and 51 MPa respectively. The decrease of thermal property and mechanical strength of MC membrane by irradiation is due to decomposition of polymeric cellulose to the lower molecular weight. This degradation hopefully improve biodegradation and resorption of MC membrane in tissue cell.